2021
DOI: 10.1002/uog.23743
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 pandemic restrictions on pregnancy duration and outcome in Melbourne, Australia

Abstract: Previous studies suggest lower rates of preterm birth during the COVID-19 pandemic. In a setting with low disease rates and strict restrictions, we followed women from conception and found a significant reduction in preterm birth that was driven by lower rates of spontaneous prematurity and stronger in women with a previous preterm birth. What are the clinical implications of this work?Women exposed to strict restrictions to mitigate the coronavirus pandemic had lower preterm birth rates than women who were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 38 publications
0
33
1
1
Order By: Relevance
“…There have been reports of a decline in preterm births after the onset of the COVID-19 pandemic in HICs 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , although findings are inconsistent. 37 , 38 , 39 , 40 , 41 , 42 Pooled estimates from a recent meta-analysis suggest a modest decrease in overall preterm birth in HICs only and also a reduction in spontaneous preterm birth but not medically indicated preterm birth, 8 although the latter finding rests on the results from only 2 hospital-based studies.…”
Section: Commentmentioning
confidence: 99%
“…There have been reports of a decline in preterm births after the onset of the COVID-19 pandemic in HICs 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , although findings are inconsistent. 37 , 38 , 39 , 40 , 41 , 42 Pooled estimates from a recent meta-analysis suggest a modest decrease in overall preterm birth in HICs only and also a reduction in spontaneous preterm birth but not medically indicated preterm birth, 8 although the latter finding rests on the results from only 2 hospital-based studies.…”
Section: Commentmentioning
confidence: 99%
“…Preterm infants (>20 weeks and < 37 weeks' gestation) born to mothers who conceived between 1 November 2019 and 29 February 2020, who were between 3 and 19 weeks pregnant at the beginning of lockdown (exposed group), compared to preterm infants conceived at the same time period the year before (control group) were included. [3] Conception was calculated based on gestational age from first day of the last menstrual period and confirmed with first trimester ultrasound. We compared neonatal outcomes of preterm infants born during lockdown in 2020 (exposed group) with preterm infants born in 2019 (control group).…”
Section: Methodsmentioning
confidence: 99%
“…While COVID-19 infection in pregnancy has been associated with an increased risk of preterm birth, [1] studies have suggested a reduction in preterm births in non-infected mothers during community lockdowns. [2,3] Very few studies have assessed what impact this has had on neonatal outcomes, and many previous studies are from countries with relatively high COVID-19 community transmission rates. Melbourne, Australia, experienced one of the world's strictest community transmission mitigation measures during two lockdowns (March-May, July-November) in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has disrupted the delivery of maternity care, with a recent systematic review concluding that global maternal and fetal outcomes had worsened during the COVID-19 pandemic. 1 Some studies have reported increases in stillbirth and reductions in preterm birth, [2][3][4][5][6][7][8] while others reported no changes. [9][10][11][12][13] These differences are likely due to multiple factors, including differences in study methodology, 14 resource setting, severity of lockdown restrictions, and COVID-19 caseload.…”
Section: Introductionmentioning
confidence: 99%